Reliability of Doubled Measurements of Power Variables - V. A. Anishchenko; A. S. Nemkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
In this article the control methods of reliability of measurements of power variables on Bayes’ criterion and multi-identification method of inexact measurements are developed.